Just the usual work : the social worlds of Ida Martin, working-class diarist - Boudreau, Michael, 1967-; Huskins, Bonnie, 1963- (McGill-Queen's University Press, 2021)
"Born in 1907, Ida Martin spent most of her life in Saint John, New Brunswick. She married a longshoreman named Allan Robert Martin in 1932 and they had one daughter. In the years that followed, Ida had a busy and varied life, full of work, caring for her family, and living her faith. Through it all, Ida found time to keep a daily diary from 1945 to 1992. Bonnie Huskins is Ida Martin's granddaughter. In Just the Usual Work, she and Michael Boudreau draw on Ida's diaries, family memories, and the history of Atlantic Canada to shed light on the everyday life of a working-class housewife during a period of significant social and political change. They examine Ida's observations about the struggles of making ends meet on a longshoreman's salary, the labour confrontations at the Port of Saint John, the role of automobiles in the family economy, the importance of family, faith, and political engagement, and her experience of widowhood and growing old. Ida Martin's diaries were often read by members of her family to reconstruct and relive their shared histories. By sharing the pages of her diaries with a wider audience, Just the Usual Work keeps Ida's memory alive while continuing her abiding commitment to documenting the past and finding meaning in the rhythms of everyday life."--